2018
DOI: 10.18805/ajdfr.dr-1277
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient composition of full fat and defatted rice bran

Abstract: The present investigation was conducted to evaluate the nutrient composition of full fat/defatted rice bran. The content of crude protein, crude fiber, ash, total carbohydrates and total dietary fiber of full fat and defatted rice bran were 11, 13.80; 10.90, 13.10; 9.20, 11.60; 49.92, 61.46; 21.63, 24.50 per cent, respectively. The amount of total Ca, P, Mg, Fe and K of full fat and defatted rice bran were 69.23, 69.80; 1331, 1345; 798, 826; 32.80, 33.31 and 1435, 1456 mg per 100g, respectively. The protein di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Carbohydrate contents were high (>50%) in all varieties, thus showing rice bran as a good source of carbohydrate. The data obtained for protein, carbohydrate and ash contents satisfied the range of basic chemical components of rice bran reported by Kumari et al (2018). High amount of fat content in rice bran also found by Rosniyana et al (2007) and Issara and Rawdkuen (2018), which lies between the range of 20% to 26%.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Carbohydrate contents were high (>50%) in all varieties, thus showing rice bran as a good source of carbohydrate. The data obtained for protein, carbohydrate and ash contents satisfied the range of basic chemical components of rice bran reported by Kumari et al (2018). High amount of fat content in rice bran also found by Rosniyana et al (2007) and Issara and Rawdkuen (2018), which lies between the range of 20% to 26%.…”
Section: Discussionsupporting
confidence: 86%
“…Despite its abundance, rice bran has been considered as an excellent source of nutrients (65% of beneficial nutrients) among other rice by-products. It is reported that rice bran was rich in protein (11-17%), carbohydrate (34-62%), fat (11-18%), crude fiber (10%), ash (9%), vitamins and trace minerals (Kumari et al, 2018). It is also an important source of antioxidants due to the presence of γ-oryzanol, tocopherols, and tocotrienols, which can help in disease prevention and promoting good health (Alauddin et al, 2017;Chakraborty & Budhwar, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There was a decrease in the moisture content after defatting of the seed flour. Kumari et al [28] also reported similar decrease in moisture contents of rice bran after defatting with values of 4.18% and 4.80% for defatted and undefatted flours, respectively. Moisture content of the flours was low when compared with 11.70% and 10.35% for raw and defatted sesame flours reported by Ogungbenle and Onoge [29].…”
Section: Proximate Composition Of Defatted and Undefatted Avocado Pear Seed Floursmentioning
confidence: 61%
“…The defatting process resulted to a significant (p<0.05) increase in ash content, which implies that the defatted avocado pear seed flour contains more minerals than undefatted seed flour. Kumari et al [28] also observed the ash content of defatted rice bran (11.60%) to be significantly higher than the full fat rice bran (9.20%). Pomeranz and Clifton [30] have recommended that ash contents of nuts, seed and tubers should fall within the range of 1.5-2.2% in order to be suitable for animal feed.…”
Section: Proximate Composition Of Defatted and Undefatted Avocado Pear Seed Floursmentioning
confidence: 94%
“…As RB is commonly used for oil extraction, the defatted rice bran (DRB) is obtained as a second by‐product . Because of the oil removal, there is a change in the relative amount of DRB nutrients, leading to higher crude protein, ash, and total dietary fiber content, greater availability of Ca and Fe, and higher protein digestibility . Prior to oil extraction, heat stabilization of the rice bran is necessary to inhibit oil deterioration by enzymatic inactivation.…”
Section: Introductionmentioning
confidence: 99%